Expression Biomarkers of Pharmacological Treatment Outcomes in Women with Unipolar and Bipolar Depression - Dmitrzak-Weglarz, Monika; Szczepankiewicz, Aleksandra; Rybakowski, Janusz; Kapelski, Paweł; Bilska, Karolina; Skibinska, Maria; Reszka, Edyta; Lesicka, Monika; Jablonska, Ewa; Wieczorek, Edyta; Pawlak, Joanna (Pharmacopsychiatry, 2021)
Introduction This study aimed to find the expression biomarkers of pharmacological treatment response in a naturalistic hospital setting. Through gene expression profiling, we were able to find differentially-expressed genes (DEGs) in unipolar (UD) and bipolar (BD) depressed women. Methods We performed gene expression profiling in hospitalized women with unipolar (n=24) and bipolar depression (n=32) who achieved clinical improvement after pharmacological treatment (without any restriction). To identify DEGs in peripheral blood mononuclear cells (PBMCs), we used the SurePrint G3 Microarray and GeneSpring software.Results After pharmacological treatment, UD and BD varied in the number of regulated genes and ontological pathways. Also, the pathways of neurogenesis and synaptic transmission were significantly up-regulated. Our research focused on DEGs with a minimum fold change (FC) of more than 2. For both types of depression, 2 up-regulated genes, OPRM1 and CELF4 (p=0.013), were significantly associated with treatment response (defined as a 50% reduction on the Hamilton Depression Rating Scale [HDRS]). We also uncovered the SHANK3 (p=0.001) gene that is unique for UD and found that the RASGRF1 (p=0.010) gene may be a potential specific biomarker of treatment response for BD.Conclusion Based on transcriptomic profiling, we identified potential expression biomarkers of treatment outcomes for UD and BD. We also proved that the Ras-GEF pathway associated with long-term memory, female stress response, and treatment response modulation in animal studies impacts treatment efficacy in patients with BD. Further studies focused on the outlined genes may help provide predictive markers of treatment outcomes in UD and BD.
Keywords: transcriptomic profile; ontology analysis; unipolar depression; bipolar depression; pharmacological treatment